The influence of hardening heat treatment modes on the crack propagation resistance of 5H2SMF die steel - Karen Yu. Shakhnazarov; Artur R. Rafikov (Frontier Materials & Technologies)
In the literature, there are virtually no data on the effect of quenching with holding in the pearlite and bainitic regions and subsequent low and high tempering of different durations on the crack propagation resistance of die steels, and the available data are contradictory. Meanwhile, a “softer” quenching with holding in the intermediate regions reduces significantly the risk of quenching cracks and deformation of dies and die tooling. In this work, samples of 5H2SMF die steel with a sharp notch and artificially induced cracks were subjected to heat treatment, including standard quenching at 910 °C in oil and quenching from 910 °C with steps at 650 °C and 340 °C with different types of tempering (200, 560, 600, and 640 °C) and different durations of time – 1, 3, 5, 7, and 14 h (for 200 °C) in order to increase the crack propagation resistance. The conducted studies allowed identifying that the data on crack propagation resistance after step quenching with holding in the pearlite transformation region and subsequent high tempering at 560, 600 and 640 °C are comparable with standard quenching in oil and high tempering at the same temperatures. The hardness after step quenching in the bainitic transformation region (340 °C) is significantly lower in all cases under different tempering conditions; therefore, it is not possible to compare crack propagation resistance with standard quenching. The optimal holding time (3 and 5 h) from the point of view of increasing crack propagation resistance after standard quenching from 910 °C in oil and low tempering at 200 °C was found.